Penerapan Rebranding Logo dan Pemanfaatan Digital Marketing Sebagai Solusi Pengembangan UMKM Keripik Barokah - Decinta Putri Ariani; Sonja Andarini (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
MSME’s Barokah is a type of family business operating in the snack food sector which has been running for four years but there has been no significant turnover growth. The aim of this research is to determine the impact of logo rebranding and the use of digital marketing. The method used in this research is a case study with data collection through observation and interviews. Research results show that rebranding will attract consumer interest as well as provide an identity for the products that will be offered. Then, marketing using digital marketing can reach a wider market, so that more people know about this product. The implication of this research is to provide innovation related to creating a new logo as an identity for MSME Barokah products, as well as creating an Instagram for the official MSME Barokah account with the hope of increasing sales through promotion of snack products managed by MSME Barokah